Optimization of Magnus Wind Turbine Blades to Increase Operational Efficiency - Tanasheva, N.; Dyusembaeva, A.; Shuyushbayeva, N.; Tussypbayeva, A.; Tleubergenova, A.; Bakhtybekova, A.; Kutumova, Zh.; Sarzhanova, I. (CFD Letters, 2025)
The problem of vortex disruption from the cylindrical blades of Magnus wind turbines is an urgent topic, which subsequently reduces the efficiency of the installation. Also, these cylindrical blades have a disadvantage in the form of low lift and high drag, as a result of which low operating efficiency is observed. Thus, the purpose of this work is a numerical study of the addition of a fixed blade to the cylindrical blades of a two-bladed wind turbine. Numerical studies were carried out for various angles of inclination of fixed blades from 0° to 60° using the Realizable k-ε turbulence model. The results of the study showed that with an increase in the angle of inclination of the fixed blade, the flow is disrupted, which is clearly visible at the maximum speed of rotation of the blades and the wind wheel, which causes a drop in lift, leading to a decrease in the efficiency of the wind turbine. Based on this, 0 degrees is the optimal angle of inclination of the fixed blade of a wind farm.
Keywords: Magnus wind turbines; cylindrical blades; efficiency; vortex disruption; angles of inclination; turbulence model